ANALISA PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA PD PASAR JAYA HWI LINDETEVES JAKARTA BARAT - Nurvi Oktiani (Universitas Bina Sarana Informatika ) (STKIP PGRI TULUNGAGUNG, 2020)
In organization must have done planning in human resource management processing to get right person for the right position. the targets of human resource management in organization management functions tell about leadership issues. The purpose of the research to determine the influence of leadership style on employee performance in PD Pasar Jaya HWI Lindeteves West Jakarta in Nursing Field. The method is used the method of quantitative analysis. The data obtained through the spread of questionnaires with Likert scale measurements, for the sample of 36 respondents from a population of 40 employees. The technique analysis is used correlation coefficient test, coefficient of determination test, and test of regression equation. Based on the calculation of correlation coefficient obtained value of 0.385 indicates that the low level of relationship between leadership styles on employee performance, the coefficient of determination shows the value indicates that the influence of leadership style on employee performance influential and the rest influenced by others factors such as work discipline, motivation, training, job satisfaction and compensation. From the regression is meaning the leadership style plus 1 unit then will increase employee performance, For advice, the organization should has to head of the nursing field continue to work, improve and understand the application of leadership style to employees it can be more conducive.